Integration Waterfall and Scrum Methodology in The Development of SIMARGA Web Application - Muay, Nikson Theys; Sediyono, Eko; Tambotoh, Johan (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
This research explores the integration of waterfall and scrum methodologies in the development of the SIMARGA web application. Integration aims to maximize the strengths of each methodology, with Waterfall contributing to planning, analysis, and initial system structure, while Scrum supports the creation of product backlog and implementation of Scrum events. The combination results in a structured and methodical product management process, simplifying task lists, and improving efficiency. The achievement of good efficiency and effectiveness in task execution is facilitated by leveraging both methodologies, reducing waste. Progress in product development and team productivity is measured through daily meetings, evaluations, and sprint reviews. Emphasis is placed on fostering strong relationships among the Scrum team, customers, and stakeholders, promoting effective communication and collaboration. However, challenges are identified in team commitment to daily meetings, which are potentially influenced by their involvement in additional business activities. Future efforts should focus on improving technological resources and maintaining software to achieve the product goals initially outlined. The effectiveness of this product development initiative can be measured using metrics such as views and user data, particularly in the Kabupaten Pegunungan Bintang.